Marketing Mix Affecting Halal food Tourism Enhancement in Ranong - Ongsara, Fasin; Chairatana, Pakamas (Rajapark Journal, 2021)
This research aimed to study 1) study personal factors of tourists about Halal food. 2) study the marketing components of Halal food in the Tourism Industry. 3) support the halal food Tourism enhancement Mueng Ranong District, Ranong Province. Data collection using a questionnaire to 384 tourists. In the questionnaire, the correlation coefficients of each question are more than The statistic used to analyze this research is statistic descriptive consist of percentage, average, and standard deviation. The results of the research The results showed that the overall satisfaction of Halal food in Ranong province from tourists is at a very good level (average = 4.36) when considering the following aspects, pointed that the most average aspect is packaging (average = 4.55) and the least average aspect is the marketing contribution (average 4.15). The results of this research have been shown that this research can be the direction to contribute halal food for Tourism in Ranong province as in Ranong province escorted Thai tourists group in Ranong Province and visited 14 famous local halal restaurants which are good taste, very good hygiene, and more variety in food. The researcher will use the information to develop the contribution for a halal restaurant to assure that all halal restaurant can be as good as customer's satisfaction and efficient, the quality of halal food will be one of the main factors that will make tourists more confident and attract more tourists in the future to Ranong province and also will help to promote tourism in Ranong province.